Exploring Ubiquitous and Mobile Computing to Leverage STEM Education: A Second Educational Scenario - Delistavrou, Konstantinos Τ.; Kameas, Achilles D. (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2022)
Our everyday life is affected by technologies like Mobile Computing, Ubiquitous Computing and the Internet of Things. Ongoing research at the Hellenic Open University aims to leverage STEM education by providing an educational framework that exploits such technologies. For this reason, a novel educational methodology is being developed. It is going to include a set of educational scenarios backed by a platform of proper software and hardware configurations. Development of the methodology continues with a second pilot scenario. Its rationale, steps and expected results are described and discussed here. The next steps of the research are defined.